Expertise économique et reconfigurations disciplinaires dans la décolonisation - Thomas Irace (Revue Internationale des Études du Développement)
Despite frequent nods to the importance of economics in the history of development, the extent of contributions from historians of economics to that literature has remained surprisingly limited. This article offers one form of explanation through a discussion of archival practices: while standard sources for the history of development economics include the papers of individual researchers and the records of international organisations, I argue that more intensive use of archives coming from (post-)colonial European national bureaucracies would lead to a better understanding of the meaning of expertise in times of decolonisation, as well as of the emergence of development economics as a specific form of knowledge in these countries. As an illustration, I discuss the Mission d’assistance économique set up by the Ministry of Overseas France in 1955, whose 1958 spinoff – the private consultancy firm SEDES – remained one of the main French organisations sending economists to the Global South until the 1980s.